PROBLEMATIKA IMPLEMENTASI PEMBIAYAAN KAFALAH DAN STRATEGI PENANGANANNYA - Siti Fatimah; Amin Awal Amarudin; Bekti Widyaningsih (LPPM Universitas KH. A. Wahab Hasbullah, 2026)
Abstract: Sharia microfinance institutions play a role in expanding access to financing through kafalah contracts as a guarantee instrument. This study aims to analyze the problems of kafalah financing implementation and its handling strategies at BMT Rizqona IKABU. The study uses a qualitative approach with a case study type. Data were obtained through interviews, observations, and documentation, then analyzed using the Miles and Huberman model. The results of the study indicate that the implementation of kafalah financing faces nine problems, namely low public understanding, default and misuse of funds, competition between financial institutions, limited human resources, employee discipline, inconsistency in the application of sharia principles, technological network disruptions, the absence of managers, bad debts. To overcome this, BMT applies certain strategies, namely education and socialization, administrative selection and salary deduction mechanisms, product and service strengthening, collaborative work, persuasive and gradual approaches, the implementation of a tiered system, coordination with the IT team, job levels, and payment rescheduling. Keywords: Kafalah Financing, Kafalah Problems, Handling Strategies